EFFECTIVENESS ENSURING OF PRIVATE MEDICAL INSTITUTIONS - КUKLINOVA, Tетіана (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study shows the importance а health care sector in Ukraine in the context of the pandemic Covid-19. The paper presents the results of study of the of medical services effectiveness. The object of research is an identification the features of the functioning of medical institutions in the conditions of the pandemic Covid-19 in Ukraine and recommendations for improving their effectiveness development. Main problems of health care sector are defined. The main features of medical institutions in Ukraine have been revealed in the work. The study deals with the key aspects of medical institutions functioning. The paper shows the importance of improving the efficiency of medical institutions. The private medical institutions complex characteristic in Ukraine are described on the basis of a detailed analysis of the problems. The results also showed the importance of private medical institutions. The study identified the requirements for them. The specificity of medical institutions in Ukraine analyzed in Ukraine. The paper deals with problems of the stimulation medical staff in Ukraine. General and specific problems for medical institutions effective development have been examined. The paper shows an effectiveness concerning the private healthcare systems in Ukraine. The study illustrates the importance of improving the efficiency of medical institutions. Proposals for healthcare systems in Ukraine are developed. The key aspects and directions of their functioning are analyzed due to the analysis of problems in Ukraine. The healthcare systems’ efficiencies recommendations is proved. This study deals foreign experience in reforming medical sector for improving its efficiency. The effective private medical services to the population in Ukraine has been shown in the presented work.
Keywords: development; stimulation; efficiency; sustainable development; medicine; health; private medical institution; health care